Moderasi Beragama dalam Perspektif Heterogenitas di Desa Jungjang Kecamatan Arjawinangun - Amirudin Amirudin; M. Abdan Karochman; Supriyatin Supriyatin (IAI Bunga Bangsa Cirebon, 2021)
One of the features of Jungjang village is the heterogeneity of religions and there are even houses of worship from several religions in one area. Religious heterogeneity means differences in systems of how to worship God Almighty and interactions with other believers. For a long time, tolerance has been deeply embedded there. Recently, the rise of religious issues is feared that it will erode the existing tolerance. To address the existing diversity so that there is no division, religious moderation is needed. Moderation or moderation, which is not extreme or not exaggerating towards a view, but must find a middle way. The method used by researchers is a qualitative type with unstructured observation and structured interviews as data collection techniques. After conducting the research for two weeks, it was found that the moderation attitude in Jungjang Village was still strong so that tolerance was still closely intertwined amid the heterogeneity that existed there. Abstrak Salah satu keistimewaan desa Jungjang yaitu adanya heterogenitas agama, bahkan terdapat rumah ibadah dari beberapa agama dalam satu wilayah. Heterogenitas agama sendiri merupakan beragamnya sistem cara beribadat kepada Tuhan Yang Maha Esa serta interaksi dengan penganut keyakinan lainnya. Sejak dahulu sikap toleransi sudah tertanam erat disana.Namun akhir-akhir ini maraknya isu-isu agama di khawatirkan akan mengikis toleransi yang sudah ada Untuk menyikapi keberagaman yang ada agar tidak timbul perpecahan maka dibutuhkan moderesi beragama. Moderasi atau moderat yaitu tidak ekstrim atau tidak berlebihan pada terhadap suatu pandangan melainkan harus mencari jalan tengahnya. Metode yang digunakan oleh peneliti adalah jenis kualitatif dengan observasi tak terstruktur dan wawancara terstruktur sebagai teknik penggumpulan datanya. Setelah melakukan penelitian selama dua minggu didapatkan hasil bahwa sikap moderasi didesa Jungjang masih kokoh sehingga toleransi masih erat terjalin ditengah heterogenitas yang ada di sana.